The annual prognostic ability of FACED and E-FACED scores to predict mortality in patients with bronchiectasis. Issue 1 (6th March 2018) - de la Rosa Carrillo, David; Athanazio, Rodrigo; Girón Moreno, Rosa Maria; Máiz Carro, Luis; Olveira, Casilda; de Gracia, Javier; Vendrell, Montserrat; Prados Sánchez, Concepción; Gramblicka, Georgina; Corso Pereira, Monica; Lundgren, Fernando; Fernandes De Figueiredo, Mara; et al.
Bronchiectasis is a disease defined by a permanent and usually progressive bronchial dilation associated with multiple exacerbations and decreased health-related quality of life [1–3]. Improvement in the current knowledge of this condition's pathophysiology has clearly highlighted its complex and heterogeneous profile, whose severity or prognosis cannot be defined using a single variable [4]. Accordingly, multidimensional scores including demographical, clinical, microbiological and radiological data have recently been developed and validated as useful tools to better evaluate the disease's severity and prognosis: FACED (forced expiratory volume in 1 s (FEV1 ), age, chronic colonisation by Pseudomonas aeruginosa, radiological extension and dyspnoea), E-FACED (FACED plus exacerbations) and the bronchiectasis severity index (BSI) [5–8]. Both FACED and E-FACED scores have shown good short-term prognostic value for predicting mortality in bronchiectasis http://ow.ly/albl30i11bv